Biological and mechanical properties of an experimental glass-ionomer cement modified by partial replacement of CaO with MgO or ZnO - Dong-Ae KIM; Hany ABO-MOSALLAM; Hye-Young LEE; Jung-Hwan LEE; Hae-Won KIM; Hae-Hyoung LEE (University of São Paulo, 2015)
AbstractSome weaknesses of conventional glass ionomer cement (GIC) as dental materials, for instance the lack of bioactive potential and poor mechanical properties, remain unsolved.Objective The purpose of this study was to investigate the effects of the partial replacement of CaO with MgO or ZnO on the mechanical and biological properties of the experimental glass ionomer cements.Material and Methods Calcium fluoro-alumino-silicate glass was prepared for an experimental glass ionomer cement by melt quenching technique. The glass composition was modified by partial replacement (10 mol%) of CaO with MgO or ZnO. Net setting time, compressive and flexural properties, and in vitrorat dental pulp stem cells (rDPSCs) viability were examined for the prepared GICs and compared to a commercial GIC.Results The experimental GICs set more slowly than the commercial product, but their extended setting times are still within the maximum limit (8 min) specified in ISO 9917-1. Compressive strength of the experimental GIC was not increased by the partial substitution of CaO with either MgO or ZnO, but was comparable to the commercial control. For flexural properties, although there was no significance between the base and the modified glass, all prepared GICs marked a statistically higher flexural strength (p<0.05) and comparable modulus to control. The modified cements showed increased cell viability for rDPSCs.Conclusions The experimental GICs modified with MgO or ZnO can be considered bioactive dental materials.